Neuromuscular electrical stimulation for physical function maintenance during hematopoietic stem cell transplantation: Study protocol. - Lindsey J Anderson; Lauren Paulsen; Gary Miranda; Karen L Syrjala; Solomon A Graf; Thomas R Chauncey; Jose M Garcia (PLoS ONE)
Hematopoietic stem cell transplantation is a common life-saving treatment for hematologic malignancies, though can lead to long-term functional impairment, fatigue, muscle atrophy, with decreased quality of life. Although traditional exercise has helped reduce these effects, it is inconsistently recommended and infrequently maintained, and most patients remain sedentary during and after treatment. There is need for alternative rehabilitation strategies, like neuromuscular electrical stimulation, that may be more amenable to the capabilities of hematopoietic stem cell transplant recipients. Patients receiving autologous HCT are being enroled in a randomized controlled trial with 1:1 (neuromuscular electrical stimulation:sham) design stratified by diagnosis and sex. Physical function, body composition, quality of life, and fatigue are assessed prior to hematopoietic stem cell transplant (prior to initiating preparatory treatment) and 24±5 days post hematopoietic stem cell transplant (Follow-up 1); physical function and quality of life are also assessed 6-months post hematopoietic stem cell transplant (Follow-up 2). The primary outcome is between-group difference in the 6-minute walk test change scores (Follow-up 1-Pre-transplant; final enrolment goal N = 23/group). We hypothesize that 1) neuromuscular electrical stimulation will attenuate hematopoietic stem cell transplant-induced adverse effects on physical function, muscle mass, quality of life, and fatigue compared to sham at Follow-up 1, and 2) Pre-transplant physical function will significantly predict fatigue and quality of life at Follow-up 2. We will also describe feasibility and acceptability of neuromuscular electrical stimulation during hematopoietic stem cell transplant. This proposal will improve rehabilitative patient care and quality of life by determining efficacy and feasibility of a currently underutilized therapeutic strategy aimed at maintaining daily function and reducing the impact of a potent and widely used cancer treatment. This trial is registered with clinicaltrials.gov (NCT04364256).